Comparison of Tryptic Fragments of von Willebrand Factor Involved in Binding to Thrombin-Activated Platelets with Fragments Involved in Ristocetin-Induced Binding and Binding to Collagen - Houdijk, Wim P M; Girma, Jen-pierre; van Mourik, Jan A; Sixma, Jan J; Meyer, Dominique (Thrombosis and Haemostasis, 1986)
Previously we have studied the binding domains on von Willebrand factor (vWF) involved in ristocetin-induced binding to platelets (ristocetin binding domain, RBD) and in the binding of vWF to collagen (collagen binding domain, CBD) using tryptic fragments of 125I-labelled vWF (21, 23). We have also reported on the RBD, CBD and the domain on vWF involved in the binding to thrombin activated platelets (thrombin binding domain, TBD) using vWF-fragments prepared by digestion with staphylococcal protease V8 (25).In the present study, we have digested 125I-vWF with TPCK-trypsin and we have performed at various times of digestion immuno-precipitation with Mab 9, the antibody inhibiting binding of vWF to thrombin activated platelets. The data were compared with the immunoprecipitation patterns simultaneously obtained with CLB-RAg 35 which inhibits binding of vWF in the presence of ristocetin and with CLB-RAg 201, which inhibits binding of vWF to collagen. At 90 min, Mab 9 and CLB-RAg 201 precipitated similar high molecular weight bands, whereas CLB-RAg 35 precipitated bands at 180 and 120 kDa. After 24 h, Mab 9 precipitated bands at 200, 155, 116 and 85 kDa; CLB-RAg 201 precipitated a band at 48 kDa and CLB-RAg 35 a band at 116 kDa. Two-dimensional electrophoresis demonstrated that the high molecular weight bands, precipitated by Mab 9 and CLB-RAg 201 at 90 min, were identical. The 116 kDa fragment recognized by CLB-RAg 35 had a different subunit composition than the 116 kDa fragment precipitated by Mab 9.These data indicate that there is an early split in the vWF subunit which yields a large fragment, containing the CBD and the TBD, and a smaller fragment with the RBD. Later, there is a split in the large fragment and the CBD and the TBD are separated. Comparison with data obtained with Staph protease V8 indicate that the CBD is located between the RBD and TBD.
Keywords: von Willebrand factor; Platelets; Ristocetin; Collagen